2016
DOI: 10.1002/ppul.23384
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index before pregnancy is associated with increased bronchodilator dispensing in early childhood: A cross‐sectional study

Abstract: Rationale Maternal prepregnancy obesity has been associated with early wheeze and childhood asthma in their offspring. Some of these studies have been in minority, urban, and disadvantaged populations using parental recall and questionnaires. The association of maternal prepregnancy obesity with bronchodilator dispensing to their offspring, in a primarily insured, non-urban, White population in the United States is unknown. Objectives and Methods We conducted a retrospective cohort study using pharmacy dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…Thus, our finding demonstrates a direct causal relationship between maternal HFD and the clinically relevant finding of AHR in adult offspring consuming a NFD. This supports observational studies associating maternal obesity and early life wheezing and asthma risk in children if a diet high in saturated fats significantly contributes to maternal obesity (Macdonald et al 2013;Pike et al 2013;Forno et al 2014;MacDonald et al 2016).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Thus, our finding demonstrates a direct causal relationship between maternal HFD and the clinically relevant finding of AHR in adult offspring consuming a NFD. This supports observational studies associating maternal obesity and early life wheezing and asthma risk in children if a diet high in saturated fats significantly contributes to maternal obesity (Macdonald et al 2013;Pike et al 2013;Forno et al 2014;MacDonald et al 2016).…”
Section: Discussionsupporting
confidence: 67%
“…Multiple studies demonstrate associations between maternal pregnancy body mass index >30 m/kg 2 and increased incidence of childhood wheezing and asthma symptoms in the offspring. A sample of over 6k mother-baby pairs clearly showed increased bronchodilator use in offspring of obese pregnancies (MacDonald et al 2016). In a prospective study, Pike et al (2013) reported associations between obese pregnancy and increased wheezing history in offspring thru age 5 years but no association with asthma or atopy.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the nonurban, white population, maternal prepregnancy obesity was associated with a 22% increase in bronchodilator dispensing in offspring in early life. Maternal prepregnancy obesity is also a prevalent risk factor for respiratory morbidity in urban, nonwhite populations [90,91].…”
Section: A New Era In Wheezy Chestmentioning
confidence: 99%
“…The fetal consequences of maternal exposure to obesity may result from direct intrauterine influence on organ development and metabolism or from subtle perturbations, including epigenetic alterations. Infants born to mothers with obesity are more likely to develop pulmonary pathologies such as chronic lung disease, reactive airways, and respiratory infections, and have altered glucose and fatty acid delivery to the lungs for surfactant production (9,21,23,24,27). In addition, infants born to mothers with obesity have altered metabolic function, which includes disruption of the hypothalamic pituitary adrenal (HPA) axis, increased leptin levels, insulin resistance, and increased blood pressure (11,31).…”
Section: Introductionmentioning
confidence: 99%